The curious heart of Ailsa Rae - Butland, Stephanie (St. Martin's Griffin, 2019)
"From Stephanie Butland, the author of The Lost for Words Bookshop, The Curious Heart of Ailsa Rae will warm you from the inside out. Ailsa Rae is learning how to live. She's only a few months past the heart transplant that-just in time-saved her life. Life should be a joyful adventure. But . . . Her relationship with her mother is at breaking point and she wants to find her father. Have her friends left her behind? And she's felt so helpless for so long that she lets polls on her blog make her decisions for her. She barely knows where to start on her own. Then there's Lennox. Her best friend and one time lover. He was sick too. He didn't make it. And now she's supposed to face all of this without him. But her new heart is a bold heart. She just needs to learn to listen to it . . "--